How useful is the machine perfusion in liver transplantation? An answer from a national survey - Scalera, Irene; De Carlis, R.; Patrono, D.; Gringeri, E.; Olivieri, T.; Pagano, D.; Lai, Q.; Rossi, M.; Gruttadauria, S.; Di Benedetto, F.; Cillo, U.; Romagnoli, R.; et al. (Frontiers in Surgery, 2022)
Machine perfusion (MP) has been shown worldwide to offer many advantages in liver transplantation, but it still has some gray areas. The purpose of the study is to evaluate the donor risk factors of grafts, perfused with any MP, that might predict an ineffective MP setting and those would trigger post-transplant early allograft dysfunction (EAD). Data from donors of all MP-perfused grafts at six liver transplant centers have been analyzed, whether implanted or discarded after perfusion. The first endpoint was the negative events after perfusion (NegE), which is the number of grafts discarded plus those that were implanted but lost after the transplant. A risk factor analysis for NegE was performed and marginal grafts for MP were identified. Finally, the risk of EAD was analyzed, considering only implanted grafts. From 2015 to September 2019, 158 grafts were perfused with MP: 151 grafts were implanted and 7 were discarded after the MP phase because they did not reach viability criteria. Of 151, 15 grafts were lost after transplant, so the NegE group consisted of 22 donors. In univariate analysis, the donor risk index >1.7, the presence of hypertension in the medical history, static cold ischemia time, and the moderate or severe macrovesicular steatosis were the significant factors for NegE. Multivariate analysis confirmed that macrosteatosis >30% was an independent risk factor for NegE (odd ratio 5.643, p = 0.023, 95% confidence interval, 1.27–24.98). Of 151 transplanted patients, 34% experienced EAD and had worse 1- and 3-year-survival, compared with those who did not face EAD (NoEAD), 96% and 96% for EAD vs. 89% and 71% for NoEAD, respectively (p = 0.03). None of the donor/graft characteristics was associated with EAD even if the graft was moderately steatotic or fibrotic or from an aged donor. For the first time, this study shows that macrovesicular steatosis >30% might be a warning factor involved in the risk of graft loss or a cause of graft discard after the MP treatment. On the other hand, the MP seems to be useful in reducing the donor and graft weight in the development of EAD.